Cannabis Use and Mental Health: A Critical Analysis of Current Research - Rusiński, Kacper; Klimas, Filip; Zatłoka-Mazur, Dorota; Zięba, Zuzanna; Potoczek , Adriana; Pudełko , Iwona; Kazubek-Fuksiewicz, Izabela; Ostrowicz, Klaudia; Lekan, Izabela (Quality in Sport, 2025)
Cannabis is one of the most widely used psychoactive substances globally. In several countries, including Canada, the Netherlands, certain U.S. states, and Australia, its possession is legal. With its growing popularity in recent years, the impact of cannabis on mental health has become a focal point of numerous scientific studies. The aim of this review was to summarize the current evidence-based knowledge on the impact of cannabis on mental health. This article explores the relationship between cannabis use and specific mental disorders. The reviewed literature was sourced from PubMed and Google Scholar using the keywords "mental health", "cannabis", "psychosis" "schizophrenia" "depression" and "cognitive functions".